Macroeconometric Evaluation of Active Labour Market Policies in Germany - A Dynamic Panel Approach Using Regional Data - Christopher Zeiss; Marco Caliendo; Uwe Blien; Reinhard Hujer (Institute for the Study of Labor (IZA), 2002)
Most evaluation studies of active labour market policies (ALMP) focus on the microeconometric evaluation approach using individual data. However, as the microeconometric approach usually ignores impacts on the non-participants, it should be seen as a first step to a complete evaluation which has to be followed by an analysis on the macroeconomic level. As a starting point for our analysis we discuss the effects of ALMP in a theoretical labour market framework augmented by ALMP. We estimate the impacts of ALMP in Germany for the time period 1999-2001 with regional data of 175 labour office districts. Due to the high persistence of German labour market data the application of a dynamic model is crucial. Furthermore our analysis accounts especially for the inherent simultaneity problem of ALMP. For West Germany we find positive effects of vocational training and job creation schemes on the labour market situation, whereas the results for East Germany do not allow profound statements.
Keywords: C33; E24; H43; J64; J68; 330; evaluation; active labour market policy; dynamic panel data model; Arbeitsmarktpolitik; Wirtschaftspolitische Wirkungsanalyse; Ökonometrisches Makromodell; Panel; Regionaler Arbeitsmarkt; Schätzung; Deutschland